Implications of holdfast availability and patchiness on juvenile seahorse (Hippocampus reidi) condition and welfare: Simulations in captivity. Issue 6 (21st November 2022) - Planas, Miquel
Abstract: Seahorses (Genus Hippocampus ; Family Syngnathidae) are iconic fish characterised by tails with prehensile capabilities, which develop after the transition from planktonic to benthonic lifestyle. As a result, seahorses remain attached to vegetal structures or other elements most of the time, both in the wild and under rearing conditions. In the present simulation study, we assessed the effect of artificial holdfast structures on the welfare of Hippocampus reidi juveniles maintained for 30 days under culture conditions. For that, both availability and patchiness of holdfast elements were considered, simulating different levels of habitat complexity. The results attained on the bioindicators assessed (survival, growth, distribution and final colouration) suggest that the viability of juveniles deprived of holdfast elements was not hampered. However, the differences observed in the final colouration of juveniles would be the result of superior welfare condition in fishes maintained in the presence of attachment structures. In addition, lower aggregation of juveniles was promoted by low complexity in simulated habitats. The results seem to indicate that habitat complexity in the wild does not affect juvenile's viability but provides better conditions for shelter and fast access to prey. However, further investigations are needed to evaluate potential detrimental effects of holdfast unavailability as a potential physiological stressor factor. Abstract :